Prophet of a new modernity: Ulrich Beck's legacy for sociology. (December 2015) - Woodman, Dan; Threadgold, Steven; Possamai-Inesedy, Alphia
Ulrich Beck was one of the most influential sociologists of recent decades. Concepts he developed – including risk society, individualization, cosmopolitanization, subpolitics and the democratization of science – are among the most cited, used and contested in contemporary sociology. In the wake of Beck's recent death, this review article revisits his key contributions and legacy. He proposed that a momentous shift to a new modernity has begun and challenged sociologists as to whether the concepts they use are up to the task of tracing this emerging dynamic. Provocatively, Beck asked whether concepts like the nation-state, family and class are functioning as 'zombie categories', continuing on in sociology but no longer relevant to social experience. We argue that Beck was not denying the significance of such social factors, but setting a challenge to the discipline to show how the key concepts of sociology can be reimagined in the face of social change.